Hubungan Oral Hygiene Dengan Mukositis Terhadap Anak Kanker Usia Sekolah Yang Menjalani Kemoterapi Di RSUP Dr. Kariadi Semarang - Eka Lutfiana; Sri Hartini; Anis Ardiyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
. Children with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (LMA) undergoing chemotherapy have one of the side effects, namely experiencing mucositis, this is also influenced by oral hygiene. The aim of the study was to determine the relationship between oral hygiene and mucositis in. The design of this study used quantitative research with descriptive analytic, namely cross sectional. The number of samples is 56 respondents with purposive sampling data collection technique. Measuring tools used Oral Hygiene questionnaire and mucositis assessment questionnaire (OAG). The results of the study were the majority of respondents with male sex 60.7%, the length of the chemotherapy period for the majority of respondents was more than 2 years 67.9%, the majority of oral hygiene obtained the most results with sufficient oral hygiene 57.1% and the majority of mucositis obtained mucositis results being 51.8%. Spearman test Rank p value obtained 0.000 so that there is a relationship between Oral Hygiene and Mucositis in cancer children, with a value of r = -0.799 very strong strength with a negative. The results of this study are expected that health workers can apply good oral hygiene for patients undergoing inpatient and outpatient care regarding the importance of good oral hygiene for children with cancer so as not to cause severe mucositis.